The changing trends and spatiotemporal clustering of hand, foot, and mouth disease in Fujian province, 2009 - 2022 - Meirong ZHAN; Zhonghang XIE; Shaojian CAI; Zhengqiang HUANG; Wu CHEN; Jianming OU (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the epidemiological characteristics, spatiotemporal clustering, and changing trends of hand, foot, and mouth disease (HFMD) in Fujian province from 2009 to 2022. MethodsData on HFMD cases in Fujian province from 2009 to 2022 were obtained from the Surveillance Reporting Management System of the China Information System for Disease Control and Prevention. Descriptive epidemiology, Joinpoint regression, spatial autocorrelation analysis, and spatiotemporal scanning were used to analyze HFMD in Fujian province. ResultsA total of 927 366 HFMD cases were reported in Fujian province from 2009 to 2022, with an average annual reported incidence rate of 172.15/100 000, severe case rate of 0.62/100 000, mortality rate of 0.018/100 000, and case fatality rate of 10.68/100 000. The reported incidence rate, severe case rate, mortality rate, and case fatality rate of HFMD all showed a trend of first increasing and then decreasing. HFMD incidence exhibited obvious seasonality, with two peaks each year, the main peak in May - June and the secondary peak in September - November. The key population was children aged < 5 years, accounting for 91.33% of all cases. Among 40 637 laboratory-confirmed cases, accounting for 4.38% of all confirmed cases, 28.93% (11 756/40 637) were positive for enterovirus A71 (EV-A71), 20.38% (8 280/40 637) were positive for coxsackievirus A16 (COX-A16), and 50.69% (20 601/40 637) were positive for other enteroviruses. Spatiotemporal clustering of HFMD existed in Fujian province (Moran's I = 0.15 - 0.56, P < 0.05). Spatiotemporal scanning detected three clusters, one primary cluster and two secondary clusters. ConclusionObvious spatiotemporal clustering of HFMD existed in Fujian province from 2009 to 2022, and the overall epidemic trend first increased and then decreased. Prevention and control of the epidemic should focus on the prefecture-level city unit and strengthen HFMD prevention and control for key populations and before the arrival of epidemic peaks.